Raymond Williams : making connections - Eldridge, J. E. T. (John Eric Thomas) (Routledge, 1994)
With brio, passion, wisdom and occasional reservations, Inglis introduces us to and evaluates Raymond Williams, the man and the icon, the brilliant cultural-political theorist, the muted social activist, the minor novelist, the compromiser and conscience of the left Victor Navasky, Publisher, The Nation.